Northanger Abbey - Austen, Jane 1775-1817 (The Cambridge edition of the works of Jane Austen, 2006)
One of the first of Jane Austen's novels to be written, and one of the last to be published, Northanger Abbey is both an amusing story of how a naive girl enters society and wins the affection of a witty young clergyman, and a high-spirited parody of the lurid gothic novels that were popular during Austen's youth. In the process it features a vivid account of social life in the late eighteenth-century Bath, and Austen's famous defence of the novel as a literary form. This edition, based on the text of the novel as published posthumously in 1818, is accompanied by explanatory notes and an appendix summarizing the plots and situations of the gothic fictions that form the basis of much of Austen's comedy. In addition there is an extensive introduction covering the context, publication, and critical history of the novel, a chronology of Austen's life, and authoritative textual apparatus.--Book jacket.